[Mukhtaṣar fī al-maʻānī - Taftāzānī, Masʻūd ibn ʻUmar, 1322-1389?
Shorter commentary by al-Taftāzānī on Talkhīṣ al-Miftāḥ by Jalāl al-Dīn al-Qazwīnī (d. 739/1338), an abridgment of the third part of Miftāḥ al-ʻulūm by al-Sakkākī (d. 626/1229), on ʻIlm al-maʻānī wa-al-bayān.
Shelfmark: Ann Arbor, University of Michigan, Special Collections Research Center, Isl. Ms. 147
Origin: Lacks dated colophon ; paper, hand, etc. suggests early 15th century, ca. 1410-1417 ; dated statement on 'title page' provides a rough terminus ante quem of 1431.
Accompanying materials: A few slips carrying notes, glosses, etc. (paginated pp.115-116, pp.183-184, and pp.205-206).
Former shelfmark: British Museum, London "No. 99. Al-Mukhtasar of Taftazani." ; "٤١٣" on tail of textblock.
Binding: Pasteboards covered in dark brown leather ; Type III binding (without flap) ; board linings in laid paper ; upper and lower covers bear border in tooled fillets and faint central motif resembling an inverted lamp ; sewn in heavy cream thread, two stations ; worked endbands in cream and dark brown or black, intact and in fair condition ; overall in poor condition with abrasion, staining, lifting of leather, delamination of boards, some negative draw in both upper and lower cover, some spine slant (slightly cocked), etc. ; repairs in tan leather.
Support: Mainly European laid paper with 8 laid lines per cm. (vertical), chain lines spaced 32 mm. apart (horizontal), and gothic 'R' (in two lines) watermark (see p.94, 176, 202, 210, 250, 260, 268 274, 300, etc. and compare Briquet 8968 dated 1410, Piccard nos. 29028, 29029, and 29031 dated 1410, Piccard no.29027 dated 1416, and Briquet 8969 dated 1417) ; also, toward close and here and there throughout codex, non-European (likely Arab), non-watermarked laid paper with grouped chain lines, perhaps in a couple of types, mainly with chain lines grouped in threes with 8-9 mm. between the chains (horizontal) and 46 mm. between the groups, 8-9 laid lines per cm. (vertical, see p.286, 318, etc.) but also with chain lines grouped in threes with 9-12 mm. between the chains (horizontal), 40-42 mm. between groups, and 7 laid lines per cm. (vertical, see p.220).
Keywords: Qazwīnī, Jalāl al-Dīn Muḥammad ibn ʻAbd al-Raḥmān, -- 1267 or 1268-1338.; Manuscripts, Arabic -- Michigan -- Ann Arbor; Arabic language -- Rhetoric -- Early works to 1800.